(untitled) (Research, Society and Development, 2020)
The objective was to evaluate and show the main impacts of excessive corporal weight, related to the complexities and clinical outcomes, caused by SARS-CoV-2. This work is based in a systematic review of published works and driven by the question: “Which are the main questions about obesity as a risk factor related to the clinical complications of COVID and severe respiratory diseases?”, the researches were realized based on MEDLINE data, through the keywords available in DeCS/MeSH: Coronavírus/Coronavirus, Obesidade/ Obesity and SARS-Cov-2/Betacoronavirus, and then through pre-fixed criteria, were selected 13 articles to make part of the same research. The severity of the infection caused by SARS-CoV-2 increased with the CMI, in patients with overweight, the needs for intensive therapy and mechanical ventilation were about 50%. The overweight can act as a deregulator, harming the lymphoids and myeloides answers, which will disrupt the immunological system and extend the infections, contributing to a higher proliferation of viral infections, as occurs in the COVID-19 pandemics, besides, those individuals usually have some pre-existing metabolic and endocrine disturbances which can contribute to the use of the immune system, inflammatory and viral pathogens. The obesity and overweight are directly related with the intensification of patients symptoms with COVID-19, trough disturbances in the immune system, lack of respiratory capability and complacency of the respiratory system, and by the presence of associated diseases to that pathology.